La frontera como dispositivo desubjetivante en Chile: la producción de la forma migrante (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
In this text we review the polysemic concept of border and its use in migration research in Chile, in order to propose an understanding of the border as a dispositif that, rather than subjectivising, is desubjectivising. To do so, we articulate the theoretical proposals of Foucault and Wieviorka, understanding the dispositif as an articulation of knowledge that institutes a division between “nationals” and “migrants” based on racist violence. Thus, the border dispositif allows us to explain not only the naturalisation of this division, but also the effects that this construction has on those who are produced as “migrants”, namely the super-exploitation of labour and dependency, which we have shown in previous research.
Keywords: Migration; Racism; Dispositif; Border; Desubjectivation